Direct Convertion Of Methane To Liquid Hydrocarbons Using HZSM-5 Zeolite Catalyst Loaded With Metal - D. D. Anggoro (Reaktor, 2003)
Methane is the main component of natural gas and this research provides the platrorm on the potential of utilizing natural gas, found abundant in Indonesia, to form gasoline. The objectives of the research are to modify HZSM-5 zeolite with a series of transition metals (Cr, Mn, Co, Ni, Cu, and Pt) and Ga , and to evaluate the performances  of these catalyst  for the single step conversion of methane to gasoline. The oxidation of methane were carried out in a micro-packed bed reactor at atmoepheric pressure, temperature 800 0C, F/W = 10440 ml/g.hr and 9%vol O2. Metals were loaded into the HZSM-5 zeolite by the wetness incipient impregnation method. The characterization results indicated that the ionic metals (Mn+) occupy the H+ position of HZSM-5 and metal loaded HZSM-5. Ni- HZSM-5, Cu- HZSM-5 and Ga- HZSM-5 gave a high methane conversion and high gasoline selectivity. Among the catalyst samles tested, Cr- HZSM-5 showed the highest  Research Octane Number (RON=86). These  catalyst have the potential  to convert natural gas to C5+ liquid hydrocarbons provided the oxidation, dehydration and oligomerization function of the metals are in balance.Keywords : direct conversion, methane, liquid hydrocarbons, metal, HZSM-5